Organisational learning in SMEs: a process improvement perspective - Matthews, Rupert Lawrence; MacCarthy, Bart L.; Braziotis, Christos (Emerald, 2016)
We investigate how Organisational Learning (OL) can occur through Process Improvement (PI) activities, leading to sustained improvements over time in the context of small and medium-sized enterprises (SMEs). We study PI practices in six engineering-oriented SMEs via interview-based case studies. We draw from a range of literature and use an OL conceptual framework, informed by Crossan et al.’s (1999) 4I framework, as an analytical lens. The OL perspective provides new insights to conceptualize the nature of PI as a multi-level practice in SMEs. Effective PI practices within SMEs are shown to be consistent with OL concepts, enabling firms to translate individually identified improvement opportunities into organisational-level changes that result in sustained benefits. A new conceptual model is presented that explains how SMEs can learn through improvement activities. The key role of management support, both operational and strategic, is highlighted. It is necessary for management to provide sufficient PI opportunities to enable and sustain beneficial learning. Management can provide additional learning opportunities by introducing new business that requires exploratory learning. Without such support, the reduction in improvement opportunities reduces the benefits that can be realised from PI. The findings provide a theoretically underpinned framework to achieve OL in engineering-oriented SMEs deriving from PI activities, highlighting the key mechanisms that enable learning from improvement activities. Further case-based, longitudinal, and survey-based research studies with firms of different types will enhance the generalisability of the findings, allowing the confirmation and extension of the new conceptual model. OL provides a multi-level perspective to understand both how smaller firms are able to undergo systematic improvements and the support required to continually improve.